2006
DOI: 10.1309/502aupr8ve67mbde
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory-Based, Hospital-Wide, Electronic Marker for Nosocomial Infection

Abstract: Faced with expectations to improve patient safety and contain costs, the US health care system is under increasing pressure to comprehensively and objectively account for nosocomial infections. Widely accepted nosocomial infection surveillance methods, however, are limited in scope, not sensitive, and applied inconsistently. In 907 inpatient admissions to Evanston Northwestern Healthcare hospitals (Evanston, IL), nosocomial infection identification by the Nosocomial Infection Marker (MedMined, Birmingham, AL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 0 publications
2
56
0
Order By: Relevance
“…The Surveillance system used in human health care centres includes laboratory diagnosis (Emori and Gaynes, 1993;Brossette et al, 2006). Many researchers in veterinary nosocomial infections also included laboratory diagnosis for confirmation (Biertuempfel et al, 1981;Mathews et al, 1996;Lobetti et al, 2002;Smarick et al, 2004;Marsh-Ng et al, 2007;Bubenik and Hosgood, 2008;Jones et al, 2009) and some researchers have not included laboratory confirmation (Nicholson, 2002;Eugster et al, 2004;Ahern et al, 2010).…”
Section: Laboratory Based Surveillancementioning
confidence: 99%
“…The Surveillance system used in human health care centres includes laboratory diagnosis (Emori and Gaynes, 1993;Brossette et al, 2006). Many researchers in veterinary nosocomial infections also included laboratory diagnosis for confirmation (Biertuempfel et al, 1981;Mathews et al, 1996;Lobetti et al, 2002;Smarick et al, 2004;Marsh-Ng et al, 2007;Bubenik and Hosgood, 2008;Jones et al, 2009) and some researchers have not included laboratory confirmation (Nicholson, 2002;Eugster et al, 2004;Ahern et al, 2010).…”
Section: Laboratory Based Surveillancementioning
confidence: 99%
“…6,12,18,23 As highlighted by Venable and Dissanaike, an electronically defined algorithm would increase reliability and reduce the variation between PPS observers. 18 Differences between potentially subjective judgements and an objective evaluation of infections in patients may also explain discrepancies seen in the present comparison of the PPSs and HAIR, e.g.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This automated, algorithm-driven approach allows for identification of hospital-acquired infections without requiring systematic chart review [10,11], and has been shown to be more accurate than administrative data. Case identification begins with microbiology laboratory findings; excludes (a) infections present on admission, (b) organisms usually present as a result of contamination, and (c) duplicate specimens; and has been validated particularly as a measure of urinary and pulmonary infections.…”
Section: Methodsmentioning
confidence: 99%